Intensifikasi Program Satu Sekolah Satu Buku untuk Meningkatkan Kemampuan Menulis Cerita pada Guru SD - Sutaji Sutaji (Journal on Education, 2021)
The goal to be achieved in this research is that teachers at SD Negeri Tenggilis Mejoyo I Surabaya have the ability to write stories in the 2021/2022 Academic Year. This action research was carried out at SD Negeri Tenggilis Mejoyo I, Tenggilis Mejoyo sub-district, Surabaya City, involving 18 teachers as research subjects from August to September 2020. This research was an action research because the author who carried out the action was the head of SD Negeri Tenggilis Mejoyo I who was responsible for fully on the development of human resources in the school environment. Story writing activity is one of the most complicated teacher professional development jobs because it requires accuracy based on the formulation of indicators. The form of story writing really depends on the indicators to be measured. Each form of this story has advantages and disadvantages, therefore the form of the story is adjusted to the indicators to be measured. Therefore, efforts are needed to improve teacher competence, especially in writing stories, one of which is through efforts to organize workshops. Workshop is a scientific meeting in a similar field (Education) to produce real work. Based on data analysis, it can be concluded from this research that the intensification of the One School One Book Program through a Workshop in writing stories is very effective. The attitudes and abilities of the teachers at Tenggilis Mejoyo I Elementary School, Tenggilis Mejoyo Subdistrict, Surabaya City have increased after the Workshop. In addition, it can also improve the ability of teachers in writing stories professionally. This can be seen in the second cycle of activities after the intensification of the One School One Book Program through the Workshop the average score obtained was 70.3. The story is said to be feasible if at least 65% of the criteria can be met. Thus, it can be stated that in the first and second cycles 100% of teachers were able to write stories that deserved to be published through the One School One Book program.